Central Conditions Mimicking Benign Paroxysmal Positional Vertigo: A Case Series. Issue 3 (July 2019) - Power, Laura; Murray, Kate; Bullus, Kristian; Drummond, Katherine J.; Trost, Nicholas; Szmulewicz, David J.
Abstract : Background and Purpose: Benign paroxysmal positional vertigo (BPPV) is the most common cause of positional vertigo. The term "benign" is consistent with a peripheral vestibular disorder that does not carry the potentially sinister sequelae of a central nervous system (CNS) cause. However, in 12% to 20% of cases, positional vertigo may be attributed to CNS pathology, including tumors of the cerebellum. Case Description: Here, we present a series of 3 cases in which positional vertigo and nystagmus were the only presenting features in 2 cases of cerebellar tumor and 1 case of obstructive hydrocephalus. Intervention: All patients underwent surgical intervention for removal of posterior fossa tumors or posterior fossa decompression for obstructive hydrocephalus. Following surgery, all 3 patients underwent a period of vestibular rehabilitation for postoperative motion sensitivity and balance impairment. Outcomes: Despite the continuing presence of central positioning nystagmus, all 3 patients recovered well, putatively with the aid of vestibular rehabilitation. Discussion: The presence of central positioning nystagmus may be the sole presenting feature of serious neurological conditions such as posterior fossa tumor. It is recommended that a diagnosis of BPPV can only be made if Dix-Hallpike or supine roll maneuver elicits nystagmus that is consistent with BPPV. Any features of the nystagmus, which are not consistent with BPPV, should raise suspicion of central pathology, and warrant further investigation. Video Abstract available for more insights from the authors (see Video Abstract, Supplemental Digital Content 1, available at: http://links.lww.com/JNPT/A265 ). Abstract : Supplemental Digital Content is Available in the Text.